Three-dimensional porous graphene / iron oxide electromagnetic shielding composite film and preparation method thereof
The three-dimensional porous graphene/iron oxide composite material was prepared by self-assembly method, which solved the problems of high filler content and poor dispersion of existing graphene electromagnetic shielding materials, and realized the preparation of high-performance electromagnetic shielding materials, improving electromagnetic wave shielding and absorption performance .
Patent Information
- Application Number
- CN202411686112.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-24
- Publication Date
- 2025-02-18
AI Technical Summary
The existing graphene electromagnetic shielding materials have problems such as high filler content and poor dispersion, which makes it difficult to form conductive grids and insufficient electromagnetic shielding performance.
Three-dimensional porous graphene/ferrous oxide composite materials were prepared by self-assembly method, and microheterogeneous interfaces were constructed using graphene oxide and nanoferrous tetraoxide to improve the dispersion of nanoferrous tetraoxide, and electromagnetic shielding performance was improved through heat treatment.
It realizes the preparation of high-performance electromagnetic shielding materials, improves electromagnetic wave shielding and absorption performance, solves the problem of difficult formation of conductive grids, and is environmentally friendly in the process and is suitable for industrial production.
Smart Images

Figure CN119463667A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional composite materials, and in particular, relates to a three-dimensional porous graphene / iron oxide electromagnetic shielding composite film and a preparation method thereof. Background Art
[0002] With the rapid development of electronic equipment and communication technology and their wide application in military, medical, industrial, commercial and other fields, the electromagnetic radiation pollution generated is becoming increasingly serious. Electromagnetic radiation pollution has become the fourth largest environmental hazard in today's society, second only to noise pollution, air pollution and water pollution. Electromagnetic radiation can affect the normal operation of electronic equipment and human health. In order to reduce or eliminate the negative impact of electromagnetic radiation, high-performance electromagnetic interference (EMI) shielding materials have attracted great attention.
[0003] The use of graphene-based materials to prepare high-efficiency, broadband, thin, flexible electromagnetic shielding materials has broad prospects. Existing graphene electromagnetic shielding materials are mostly formed by polymerizing graphene as a filler with polymers, but the filled type has disadvantages such as high filler content and poor dispersibility; due to the strong van der Waals force and electrostatic force in the graphene layer, it is difficult to interact with the polymer, and too much graphene is easy to agglomerate, making it difficult to form a conductive grid to the maximum extent. Summary of the invention
[0004] The purpose of the present invention is to provide a method for successfully synthesizing a three-dimensional graphene / ferroferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding material by means of a self-assembly method. The purpose of the present invention is also to provide a high-performance 3D rGO / Fe3O4 slurry-coated electromagnetic shielding film that is environmentally friendly and suitable for industrial production.
[0005] The present invention uses graphene oxide and nano-ferroferric oxide as raw materials to prepare a porous 3D rGO / Fe3O4 composite material, improves the dispersibility of nano-ferroferric oxide, and further improves the electromagnetic shielding performance of the composite material by modifying the prepared composite material through heat treatment; uses a dispersant-assisted method to prepare a uniform-sized Fe3O4 nanosphere aqueous dispersion, and then uses a graphene oxide reduction self-assembly method to construct a microscopic graphene oxide-nano Fe3O4 heterogeneous interface to obtain a "ball (Fe3O4)-net (3D rGO)" structure. By constructing a ferroferric oxide nanosphere-three-dimensional graphene heterogeneous interface structure and an appropriate heat treatment process, the electromagnetic wave shielding and absorption performance of the 3DrGO / Fe3O4 composite electromagnetic shielding material is improved, thereby achieving the goal of preparing a high-performance graphene composite electromagnetic shielding material.
[0006] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0007] The object of the present invention is to provide a method for preparing a three-dimensional porous graphene / iron oxide electromagnetic shielding composite film, comprising the following steps:
[0008] Step 1, ultrasonically dispersing graphene oxide in ionized water, and opening the graphene oxide flakes by ultrasonic action to obtain a graphene oxide solution;
[0009] Step 2, ultrasonically dispersing nano-ferroferric oxide into deionized water to obtain a ferroferric oxide dispersion;
[0010] Step 3, adding dispersant in batches, dispersing each batch evenly, and after dispersion is complete, continuing ultrasonication for a certain period of time to obtain a mixed solution;
[0011] Step 4, subjecting the graphene oxide solution obtained in step 1 to ultrasonic treatment for a certain period of time, adding the mixed solution obtained in step 3 under strong stirring conditions, and then ultrasonic treatment for a certain period of time;
[0012] The nano-Fe3O4 particles are compounded with graphene oxide through step 4.
[0013] Step 5, then add ascorbic acid, seal, perform hydrothermal reduction, cool to room temperature after the reaction is completed, change water for multiple soaking, crush, filter and wash at least three times, spread evenly and freeze-dry to obtain a 3D rGO / Fe3O4 composite material;
[0014] Step 6, heat-treating the 3D rGO / Fe3O4 composite material under inert gas protection, then mixing it with polyvinyl pyrrolidone, and dry-grinding it to obtain a powder;
[0015] After heat treatment, the graphite layered structure of the reduced graphene oxide is more fully reduced, the oxygen-containing functional groups are decomposed in large quantities, the lattice defects are largely eliminated, and the structure is more complete; the time and temperature of the heat treatment are controlled.
[0016] Step 7: Add waterborne polyurethane to the powder in batches. After the addition is completed, continue stirring for a certain period of time, then coat it on copper foil or other types of substrates such as PET, PI, conductive cloth, and dry it; thus, the composite film is obtained.
[0017] Furthermore, in step 1, the concentration of the graphene oxide solution is 1 mg / mL to 10 mg / mL; the ultrasonic frequency is 300w to 1000w, and the ultrasonic time is 2h to 5h.
[0018] Furthermore, in step 2, the concentration of the ferroferric oxide dispersion is 0.5 mg / mL to 5 mg / mL; the ultrasonic frequency is 300w to 1000w, and the time is 2h to 5h.
[0019] Furthermore, in step 3, the dispersant is hydroxymethyl cellulose, and the amount of the dispersant is 0.5% to 5%.
[0020] Furthermore, the stirring speed of the strong stirring is 1000 rpm to 2500 rpm.
[0021] Furthermore, in step 5, hydrothermal reduction is carried out at 60°C to 100°C for 1h to 3.5h; and the freeze-drying is carried out in a vacuum freeze drying oven with the temperature controlled at -10°C to -50°C for 50h to 82h.
[0022] Furthermore, in step 6, the inert gas is argon, and the heat treatment is performed at 500° C. to 1000° C. for 1.5 h to 5 h in a tubular furnace.
[0023] Furthermore, in step 7, the mass ratio of solid to liquid is 1:(6-15).
[0024] Further, in step 7, drying is performed at 40° C. to 110° C. for 2 h to 8 h in a vacuum drying oven.
[0025] Furthermore, in step 7, coating is performed using a coater, and the coating thickness is 30 μm-400 μm.
[0026] A three-dimensional porous graphene / iron oxide electromagnetic shielding composite film prepared by any of the above methods.
[0027] The lattice of Fe3O4 particles is a complicated face-centered cubic (composed of oxygen atoms) structure. 3+ Occupies the tetrahedral gap (A site), Fe 2+ and Fe 3+ Together they occupy the octahedral gap (B position), and in the present invention, Fe 2+ and Fe 3+Through the super exchange of oxygen ions, Fe3O4 particles are transformed into ferrimagnetic particles. The present invention improves the absorption loss and multiple reflection performance of graphene by structural regulation. The present invention modifies graphene and optimizes the process to effectively improve the dispersibility and conductivity, which is to reduce costs and improve shielding effectiveness. The present invention designs a graphene composite material with a new structure from the perspective of structuring and composite. First, the solvent thermal reduction method is used to reduce graphene oxide, and a three-dimensional graphene (3D rGO) network is successfully prepared in a safe and environmentally friendly manner. The three-dimensional structure further improves the problem of easy aggregation of graphene, while maintaining the good conductivity of two-dimensional materials. Then, a three-dimensional porous 3D rGO / Fe3O4 composite material is successfully prepared by a self-assembly method. The three-dimensional porous structure can reduce the density of the composite material on the one hand, and on the other hand, the porous structure ensures that electromagnetic waves can penetrate into the material, and the internal pores synergistically enhance the impedance mismatch at the interface between the material body and the free space. In addition, through process optimization, a set of scientific and efficient large-scale and customized preparation processes are summarized, which are environmentally friendly and suitable for industrial production.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention is a method combining graphene oxide reduction self-assembly, self-assembled nanoparticle capture, steam reduction and tube furnace heat treatment to complete the preparation of a three-dimensional porous graphene / ferroferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film. The advantages are that the raw materials are generally available, the cost is low, the preparation process is safe, and it is simple and easy to operate; when the graphene oxide is reduced, the surface epoxy functional groups and hydroxyl groups are gradually removed, and the continuously enhanced van der Waals force and π-π stacking effect increase the number of crosslinks between graphenes, thereby generating a three-dimensional graphene (3D rGO) network. The Fe3O4 nanospheres are uniformly dispersed in deionized water by a dispersant-assisted method, and then a microscopic heterogeneous interface "sphere (Fe3O4)-net (3D rGO)" structure is constructed with graphene oxide by a liquid phase co-reduction method. The coating formula and coating process of the 3D rGO / Fe3O4 composite electromagnetic shielding material are optimized to improve the comprehensive performance of the electromagnetic shielding product. The development goal of preparing multi-purpose and high-performance electromagnetic shielding products is achieved.
[0030] The preparation process of the invention is simple and easy to control, the raw material cost is low, easy to obtain, and environmentally friendly; it can prepare a graphene-based composite electromagnetic shielding material that is light, high-strength, stable, flexible, and has high electromagnetic shielding efficiency.
[0031] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A real photo of the three-dimensional graphene / ferroferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of the present invention;
[0033] Figure 2 A photo of the bending of the three-dimensional graphene / ferroferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of the present invention;
[0034] Figure 3 Infrared spectrum comparison diagram of Example 1 of the present invention;
[0035] Figure 4 The electromagnetic shielding effectiveness comparison spectrum of Example 1 of the present invention;
[0036] Figure 5 Microscopic morphology and element surface distribution diagram of Example 1 of the present invention under a scanning electron microscope. DETAILED DESCRIPTION
[0037] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0038] Example 1: The preparation method of the three-dimensional porous graphene / iron oxide electromagnetic shielding composite film in this example is achieved by the following steps:
[0039] Step 1, under the condition of an ultrasonic frequency of 600w, 0.95g of graphene oxide is uniformly dispersed in 400mL of deionized water to obtain a graphene oxide solution;
[0040] Step 2: Evenly disperse 0.05 g of nano-ferroferric oxide into 100 mL of deionized water under an ultrasonic frequency of 600 W to obtain a ferroferric oxide dispersion;
[0041] Step 3, disperse 0.0025g HMC in small amounts evenly on the surface of the ferroferric oxide dispersion three times, and after the dispersion is complete, continue ultrasonication for 30 minutes to obtain a mixed solution;
[0042] Step 4, ultrasonically treat the graphene oxide solution obtained in step 1 (ultrasonic frequency is 600w) for 60min, under strong stirring (stirring speed is 2000rpm), then add the mixed solution, and then ultrasonically treat for 30min under (ultrasonic frequency is 600w);
[0043] Step 5, then add 0.9g ascorbic acid (VC), seal with plastic wrap, heat to 95°C, and perform hydrothermal reduction under heat preservation for 2h. After the reaction is completed, cool to room temperature, change water for several times, and crush every other day. Filter and wash three times, evenly spread in a glass dish, place in a vacuum freeze drying box, and freeze-dry at -40°C for 72h to obtain a 3D rGO / Fe3O4 composite material;
[0044] Step 6: Compact the freeze-dried powder into a porcelain boat as much as possible, put it into a tube furnace, and heat treat it at 800°C for 3 hours under argon atmosphere protection conditions;
[0045] Step 7. Take 1 g of the 3D rGO / Fe3O4 composite material after heat treatment in step 6, mix it with 0.05 g of polyvinyl pyrrolidone K30 (PVP), add it to a mortar and dry grind it for 40 minutes, put the ground powder into a 100 mL beaker, take 9 g of waterborne polyurethane, add 5 g, 2 g, and 2 g into the beaker three times under stirring conditions for 5 min, 10 min, and 15 min, continue stirring for 300 min, apply it on a copper foil with a coater, put it in a drying oven and dry it for 1 hour, and after it is completely dried, cut it into 4 cm×4 cm samples.
[0046] The actual photo of the three-dimensional graphene / ferroferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of the present invention is as follows: Figure 1 shown.
[0047] The actual photo of the bending of the three-dimensional graphene / ferroferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of the present invention is as follows Figure 2 shown.
[0048] The infrared spectrum comparison diagram after heat treatment of Example 1 of the present invention is as follows Figure 3 As shown by Figure 3 It can be seen that the heat-treated sample has a wavelength of 3750 cm -1 The characteristic peak of 1360cm is greatly weakened because the OH chemical bond breaks at high temperature and gas escapes. -1 The COC characteristic peak at the site is also significantly weakened. The infrared spectrum shows that the residual oxygen-containing functional groups are further reduced after heat treatment, the graphene defects in the sample are reduced, and the structure is more complete.
[0049] The electromagnetic shielding effectiveness comparison spectrum of Example 1 of the present invention after heat treatment is as follows Figure 4 As shown. Figure 4 It can be seen that the electromagnetic shielding effectiveness test results in the X-band. The test frequency is 8.2GHz~12.4GHz, and the test sample size is 40mm×40mm. It can be seen from the figure that the average value of electromagnetic shielding effectiveness (SET) reaches more than 70dB.
[0050] The SEM electron microscope photo of Example 1 of the present invention is as follows Figure 5 As shown, (a) is the 3D rGO sample, and (b) is the 3DrGO / Fe3O4 microporous structure. Figure 5 It can be seen that the 3D graphene has a regular morphology, the proportion of nano-iron tetroxide added is small, and no agglomeration phenomenon is observed. Nano-iron tetroxide is evenly dispersed on the surface of the assembled graphene and in the gaps between the sheets. This shows that the composite effect of 3D rGO and Fe3O4 is good, and the macroscopic state of the powder particles is also improved.
[0051] Embodiment 2: The preparation method of the three-dimensional porous graphene / iron oxide electromagnetic shielding composite film in this embodiment is achieved by the following steps:
[0052] Step 1, under the condition of an ultrasonic frequency of 600w, 0.4g of graphene oxide is uniformly dispersed in 350mL of deionized water to obtain a graphene oxide solution;
[0053] Step 2, under the condition of ultrasonic frequency of 600w, 0.1g of nano-ferroferric oxide is uniformly dispersed in 150mL of deionized water to obtain a ferroferric oxide dispersion;
[0054] Step 3, disperse 0.005 g HMC in small amounts evenly on the surface of the ferroferric oxide dispersion three times, and after the dispersion is complete, continue ultrasonication for 30 minutes to obtain a mixed solution;
[0055] Step 4, ultrasonically treat the graphene oxide solution obtained in step 1 (ultrasonic frequency is 600w) for 60min, under strong stirring (stirring speed is 2000rpm), then add the mixed solution, and then ultrasonically treat for 30min under (ultrasonic frequency is 600w);
[0056] Step 5, then add 0.9g ascorbic acid (VC), seal with plastic wrap, heat to 95°C, and perform hydrothermal reduction under heat preservation for 2h. After the reaction is completed, cool to room temperature, change water for several times, and crush every other day. Filter and wash three times, evenly spread in a glass dish, place in a vacuum freeze drying box, and freeze-dry at -40°C for 72h to obtain a 3D rGO / Fe3O4 composite material;
[0057] Step 6: Compact the freeze-dried powder into a porcelain boat as much as possible, put it into a tube furnace, and heat treat it at 800°C for 3 hours under argon atmosphere protection conditions;
[0058] Step 7. Take 1 g of the 3D rGO / Fe3O4 composite material after heat treatment in step 6, mix it with 0.05 g of polyvinyl pyrrolidone K30 (PVP), add it to a mortar and dry grind it for 40 minutes, put the ground powder into a 100 mL beaker, take 9 g of waterborne polyurethane, add 5 g, 2 g, and 2 g into the beaker three times under stirring conditions for 5 min, 10 min, and 15 min, continue stirring for 300 min, apply it on a copper foil with a coater, put it in a drying oven and dry it for 1 hour, and after it is completely dried, cut it into 4 cm×4 cm samples.
[0059] After testing, the average magnetic shielding effectiveness (SET) value reached 77dB.
[0060] Embodiment 3: The preparation method of the three-dimensional porous graphene / iron oxide electromagnetic shielding composite film in this embodiment is achieved by the following steps:
[0061] Step 1, under ultrasonic conditions (ultrasonic frequency is 600w), 0.9g of graphene oxide is uniformly dispersed in 350mL of deionized water to obtain a graphene oxide solution;
[0062] Step 2, under ultrasonic conditions (ultrasonic frequency is 600w), 0.1g of nano-ferroferric oxide is uniformly dispersed in 150mL of deionized water to obtain a ferroferric oxide dispersion;
[0063] Step 3, 0.005 g of hydroxymethyl cellulose (HMC) was evenly dispersed on the surface of the ferroferric oxide dispersion in small amounts three times, and after the dispersion was complete, ultrasonication was continued for 30 minutes to obtain a mixed solution;
[0064] Step 4, ultrasonically treat the graphene oxide solution obtained in step 1 (ultrasonic frequency is 600w) for 60min, under strong stirring (stirring speed is 2000rpm), then add the mixed solution, and then ultrasonically treat for 30min under (ultrasonic frequency is 600w);
[0065] Step 5, then add 0.9g ascorbic acid (VC), seal with plastic wrap, heat to 95°C, and perform hydrothermal reduction under heat preservation for 2h. After the reaction is completed, cool to room temperature, change water for several times, and crush every other day. Filter and wash three times, evenly spread in a glass dish, place in a vacuum freeze drying box, and freeze-dry at -40°C for 72h to obtain a 3D rGO / Fe3O4 composite material;
[0066] Step 6: Compact the freeze-dried powder into a porcelain boat as much as possible, put it into a tube furnace, and heat treat it at 800°C for 3 hours under argon atmosphere protection conditions;
[0067] Step 7. Take 1 g of the 3D rGO / Fe3O4 composite material after heat treatment in step 6, mix it with 0.05 g of polyvinyl pyrrolidone K30 (PVP), add it to a mortar and dry grind it for 40 minutes, put the ground powder into a 100 mL beaker, take 9 g of waterborne polyurethane, add 5 g, 2 g, and 2 g into the beaker three times under stirring conditions for 5 min, 10 min, and 15 min, continue stirring for 300 min, apply it on a copper foil with a coater, put it in a drying oven and dry it for 1 hour, and after it is completely dried, cut it into 4 cm×4 cm samples.
[0068] After testing, the average magnetic shielding effectiveness (SET) value reached 77dB.
Claims
1. A method for preparing a three-dimensional porous graphene / iron oxide electromagnetic shielding composite film, characterized in that: The preparation method comprises the following steps: Step 1, ultrasonically dispersing graphene oxide in deionized water to obtain a graphene oxide solution; Step 2, ultrasonically dispersing nano-ferroferric oxide into deionized water to obtain a ferroferric oxide dispersion; Step 3, adding dispersant in batches, dispersing each batch evenly, and after dispersion is complete, continuing ultrasonication for a certain period of time to obtain a mixed solution; Step 4, subjecting the graphene oxide solution obtained in step 1 to ultrasonic treatment for a certain period of time, adding the mixed solution under strong stirring conditions, and then ultrasonic treatment for a certain period of time; Step 5, then add ascorbic acid, seal, perform hydrothermal reduction, cool to room temperature after the reaction is completed, change water for multiple soaking, crush, filter and wash at least three times, spread evenly and freeze-dry to obtain a 3D rGO / Fe3O4 composite material; Step 6: heat-treating the 3D rGO / Fe3O4 composite material under inert gas protection, then mixing it with polyvinyl pyrrolidone, and dry-grinding it to obtain a powder. Step 7: Add waterborne polyurethane to the powder in batches. After the addition is completed, continue stirring for a certain period of time, then coat it on copper foil or other types of substrates such as PET, PI, conductive cloth, and dry it; thus, the composite film is obtained.
2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of the graphene oxide solution is 1 mg / mL to 10 mg / mL; the ultrasonic frequency is 300w-1000w, and the ultrasonic time is 2h to 5h.
3. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the ferroferric oxide dispersion is 0.5 mg / mL to 5 mg / mL; the ultrasonic frequency is 300w-1000w, and the time is 2h to 5h.
4. The preparation method according to claim 1, characterized in that: In step 3, the dispersant is hydroxymethyl cellulose, and the amount of the dispersant is 0.5% to 5%.
5. The preparation method according to claim 1, characterized in that: The stirring speed of strong stirring is 1000-2500rpm.
6. The preparation method according to claim 1, characterized in that: In step 5, hydrothermal reduction is performed at 60°C to 100°C for 1h to 3.5h; the freeze-drying is performed in a vacuum freeze drying oven with the temperature controlled at -10°C to -50°C for 50h to 82h.
7. The preparation method according to claim 1, characterized in that: In step 6, the inert gas is argon, and the heat treatment is performed at 500° C. to 1000° C. for 1.5 h to 5 h.
8. The preparation method according to claim 1, characterized in that: In step 7, the mass ratio of solid to liquid is 1:(6-15).
9. The preparation method according to claim 1, characterized in that: In step 7, the coating thickness is 30 μm-400 μm, and the coating is dried at 40° C. to 110° C. for 2 h to 8 h.
10. A three-dimensional porous graphene / iron oxide electromagnetic shielding composite film prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Graphene-loaded nanometer Fe3O4 / aqueous polyurethane composite magnetic conductive wave absorbing coating material and preparation method thereof
CN104962185A
Macroscopic three-dimensional ultralight Fe3O4 doped graphene aerogel composite material and preparation method
CN105000886A
Hyperelastic magnetic-heat three-dimensional graphene support composite material and preparation method thereof
CN108689399A
Graphene / ferroferric oxide composite material and preparation method and application thereof
CN110678055A
Preparation method of Fe3O4 / rGO / polyimide aerogel electromagnetic wave-absorbing material
CN114752101A
Cited By
Radar wave-absorbing coating and preparation method thereof
CN120888230A